Quality in using Google Classroom as an Online Learning Media in Arabic Lesson - Dawam Cahya; Hilyah Ashoumi (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to describe the quality of the use of Google Classroom as an online learning medium for Arabic subjects. This study uses descriptive qualitative research with an analytical approach to online learning using google classroom. The data in this study were obtained by means of interviews and distributing questionnaires on the quality of using google classroom as a learning medium. The results of observations also show that online learning using Google Classroom has a very good impact. With the features in Google Classroom, it is very helpful in this online learning process. Online learning using Google Classroom is well prepared, starting from teacher planning, student readiness, and learning materials. It is evident from the results of the questionnaire that has been distributed, it concludes that the use of Google Classroom in online learning is very effective. And it helps a lot in online learning.